Diversity of Vaginal Microbiome in Pregnancy: Deciphering the Obscurity - Gupta, Parakriti; Singh, Mini P.; Goyal, Kapil (Frontiers in Public Health, 2020)
Human microbiota plays an indispensable role in physiology, nutrition and most significantly, in imparting immunity. The role of microbiota has remained cryptic for years, until recently meticulous studies revealed the interaction and dynamics of these microbial communities. This diversified state is governed by hormonal, behavioral and physio-chemical changes in the genital tract. Many inclusive studies have revealed “Lactobacillus” to be the most dominant member of vaginal flora in most of the healthy, reproductive age group and pregnant females. A total of five community state types have been described, out of which four are dominated by Lactobacillus while the fifth one by facultative or strict anaerobic species. A variation between species stability and gestational age has also been revealed. Studies have divulged a significant higher stability of vaginal microbiota in early stages of pregnancy and the same increased subsequently. Inter-species and racial variation has shown women belonging to White, Asian, and Caucasian race to harbor more of the anaerobic flora. The vaginal microbiome in pregnancy play a significant role in preterm and spontaneous labor. This Lactobacillus-rich microbiome falls tremendously, becoming more diverse in post-partum period. Apart from these known bacterial communities in human vagina, other microbial communities have also been traced. The major fragment is constituted by vaginal viral virome and very little information exists in relation to vaginal mycobiome. Studies have revealed the abundance of ds DNA viruses in vaginal microbiome, followed by ssDNA, and few unidentified viruses. The eukaryotic viruses detected were very few, with Herpesvirales, and Papillomaviridae being the only pathogenic ones. This flora is transmitted to infants either via maternal gut, vagina or breast milk. Recent studies have given an insight for vaginal microbiome, dissociating the old concept of “healthy” and “diseased.” However, more extensive studies are required to study evolution of virome and mycobiome in relation to their association with bacterial communities; to establish and decode full array of vaginal virome under the influence of genotypic and environmental factors, using novel bioinformatic, multi-omic, statistical model, and CRISPR/Cas approaches.